How and how well have older people been engaged in healthcare intervention design, development or delivery using co‐methodologies: A scoping review with narrative summary. (25th October 2020) - Cowdell, Fiona; Dyson, Judith; Sykes, Michael; Dam, Rinita; Pendleton, Rose
Abstract: Co‐methodological working is gaining increasing traction in healthcare, but studies with older people have been slower to develop. Our aim was to investigate how and how well older people have been engaged in healthcare intervention design, development or delivery using co‐methodologies. We conducted a systematic search of four electronic databases to identify international literature published between 2009 and November 2019. We included peer‐reviewed empirical research of any design. Three authors screened papers. Our review is reported in accordance with the Joanna Briggs Institute manual for scoping reviews, we have referred to the preferred reporting items for systematic reviews and meta‐analyses statement. We data extracted to a bespoke spreadsheet and used the Co:Create Co‐production Matrix to guide quality appraisal. Included studies ( n  = 48) were diverse in nature of interventions, co‐methodologies and reporting. We offer a narrative summary of included papers. Establishing how older people were engaged in co‐methodological work was largely straightforward. How well this was done was more challenging, however we have identified gems of good practice and offered directions for future practice. The Co:Create Co‐Production Matrix was the best fit for evaluating papers, however it is not intended as a measure per se. In essence we argue that notions of 'best' and 'scores' are an oxymoron in co‐methodological working, what is important that: (a) researchers embrace these methods, (b) incremental change is the way forward, (c) researchers need to do what is right for people and purpose and (d) have time to consider and articulate why they are choosing this approach and how best this can be achieved for their particular situation. Future evaluation of participant's experience of the process would enable others to learn about what works for who and in what circumstances.